The Development and Validation: The Scale of Subjective Well-Being for Mother (SSWB-M) - prastuti, endang; prastuti, endang; Tairas, Mareyke Maritje Wagey; Hartini, Nurul (Universitas Ahmad Dahlan, 2018)
AbstractÂ The objectives of this study were to develop the Scale of Subjective Well-Being for Mother (SSWB-M), and to examine the psychometric properties of SSWB-M that have been developed. The results of this study show that The developed Scale of Subjective Well-Being for Mother (SSWB-M) consists of The Scale of Life Satisfaction in Family Domain (SLS-FD) and the Positive and Negative Affect Scale in Family Domain (PANAS-FD).The Scale of Life Satisfaction in Family Domain (SLS-FD) showing a match with chi-square = 147.190 (p = 0.118), GFI = 0.881, AGFI = 0.805, CFI = 0.984, TLI = 0.977, and RMSEA = 0.039 describes a good goodness of fit. Overall reliability has a high value of Alpha Cronbach coefficient, which is 0.892, and composite reliability of 0.984. Positive - Negative Affect Scale in Family Domain (PANAS-FD) shows the results of evaluation of fit model Â with chi square = 46,450 (p = 0,332), GFI = 0,925, AGFI = 0,886, CFI = 0,995, TLI = 0,994, and RMSEA = 0,028 describes that the goodness of fit is good. Overall, on PANAS-FD have the composite reliability is 0.950, and the Alpha Cronbach is 0.763. The Scale of Subjective Well-Being for Mother (SSWB-M), the two sub-scales have high validity and reliability, therefore it can be used to measure subjective well-being in young mothers.Â Keywords: Development, validation, SSWB-M